2014
DOI: 10.1038/npp.2014.180
|View full text |Cite
|
Sign up to set email alerts
|

Amylin Modulates the Mesolimbic Dopamine System to Control Energy Balance

Abstract: Amylin acts in the CNS to reduce feeding and body weight. Recently, the ventral tegmental area (VTA), a mesolimbic nucleus important for food intake and reward, was identified as a site-of-action mediating the anorectic effects of amylin. However, the long-term physiological relevance and mechanisms mediating the intake-suppressive effects of VTA amylin receptor (AmyR) activation are unknown. Data show that the core component of the AmyR, the calcitonin receptor (CTR), is expressed on VTA dopamine (DA) neurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
105
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(117 citation statements)
references
References 72 publications
(96 reference statements)
9
105
3
Order By: Relevance
“…Thus, we argue that the present findings do not fall under the scope of calcium levels regulation, but they are a result of sCT's central action. Although there is no robust evidence that sCT crosses the blood-brain barrier effectively, there are data showing that peripheral sCT did not affect food intake in rats with a knocked down calcitonin receptor in the VTA but decreased food intake in control (Mietlicki-Baase et al 2015b). Moreover, a recent study showed that peripherally administered sCT decreased VTA-evoked phasic dopamine release in the NAc (Whiting et al 2017), supporting our notion that sCT acts centrally on the mesolimbic dopamine system to regulate dopamine neurotransmission.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Thus, we argue that the present findings do not fall under the scope of calcium levels regulation, but they are a result of sCT's central action. Although there is no robust evidence that sCT crosses the blood-brain barrier effectively, there are data showing that peripheral sCT did not affect food intake in rats with a knocked down calcitonin receptor in the VTA but decreased food intake in control (Mietlicki-Baase et al 2015b). Moreover, a recent study showed that peripherally administered sCT decreased VTA-evoked phasic dopamine release in the NAc (Whiting et al 2017), supporting our notion that sCT acts centrally on the mesolimbic dopamine system to regulate dopamine neurotransmission.…”
Section: Discussionsupporting
confidence: 56%
“…In fact, amylin and sCT express their anorexigenic effects through central mechanisms involving the area postrema and the nucleus of the solitary tract (Lutz et al 2001a;Potes & Lutz 2010;Braegger et al 2014). Recent studies show that amylin receptors in the NAc, VTA and LDTg (Baisley & Baldo 2014;Mietlicki-Baase et al 2015a;Reiner et al 2017) and more specifically amylin receptors on ventral tegmental dopaminergic neurons mediate the effect of sCT on the control of energy balance (Mietlicki-Baase et al 2013;Mietlicki-Baase et al 2015b). Thus, amylin's action on the mesolimbic dopamine system suggests a potential role that extends beyond regulation of natural rewards, and tenuous evidence supports a possible amylinergic mediation of artificial rewards, such as alcohol.…”
Section: Introductionmentioning
confidence: 99%
“…These mechanisms certainly involve activation by proximal cues including orosensory stimulation, pre-absorptive mechanisms, and post-absorptive mechanisms [21,23,42,54,60]. Multiple hormones, among them ghrelin, insulin, amylin, and glucagon-like peptide 1, that are released peripherally interact either directly or indirectly with the mesolimbic dopamine pathway [15,[80][81][82][83][84]. Cells located both peripherally and centrally are able to respond to changes in glucose concentration including intestinal cells and dopamine neurons and their inputs [60,85,86].…”
Section: Mechanisms Of Dopamine Neuron Activation and Plasticitymentioning
confidence: 99%
“…Leptin (NHPP) was dissolved in 0.01 M sodium bicarbonate. The selected doses of drugs were based on the literature (17,32,33).…”
Section: Subjectsmentioning
confidence: 99%
“…Recent studies have established the VTA as a physiologically and pharmacologically relevant site of action for the intake-suppressive effects of amylin (32,33). Furthermore, leptin has been shown to act independently in the VTA to induce hypophagia in a physiologically relevant manner (14,17).…”
mentioning
confidence: 99%